Prioritized Health Literacy and Clear Communication Practices For Health Care Professionals - Cliff Coleman; Stan Hudson; Ben Pederson (SLACK Incorporated, 2017)
Background: Health care professionals need more and better training about health literacy and clear communication to provide optimal care to populations with low health literacy. A large number of health literacy and clear communication practices have been identified in the literature, but health professions educators, administrators, and policymakers have lacked guidance regarding which practices should be prioritized among members of the health care workforce. Objective: This study sought to prioritize recommended health literacy and clear communication practices for health care professionals. Methods: A Q-sort consensus method was used among 25 health literacy experts to rank a previously identified list of 32 health literacy and clear communication practices for health care professionals. Mean ratings for each of the 32 practices were compared using t-tests. Key Results: Mean ratings for the 32 practices fell along a spectrum from higher to lower importance. The eight top-rated practices formed a cluster, and seven of these items demonstrated clear consensus, whereas one item may have been influenced by one or more outlier rankings. Conclusions: Although a large number of health literacy and clear communication practices have been recommended in the literature for health care professionals, this is the first known study to rank such practices in terms of importance. The top-rated items can be considered a core set of practices that all health care professionals should learn and routinely use in clinical settings. These consensus opinion results will help health professions educators, administrators, and policymakers to direct potentially limited resources toward improving training in patient-centered communication, and when designing curricula, practice standards, care delivery models, and policies for health care professionals and systems to improve patient outcomes. Future studies should empirically confirm the relative value of the ranked items in terms of patient-centered outcomes.